Perancangan Media Pembelajaran Komponen Pasif dan Aktif Pada SMK Muhammadiyah 3 Weleri Dengan Metode MDLC - Dika Wahyu Pratama; Edy Siswanto (JURNAL TEKNIK INFORMATIKA DAN MULTIMEDIA, 2021)
Quality education can be achieved with the means to carry out learning. One of the facilities used is to use learning aids or learning media. Learning media is an integral part of the learning process in the classroom. SMK Muhammadiyah 3 Weleri which is located at Jl Bahari No. 345 Weleri sub-district, Kendal district, in delivering basic electricity and electronics lessons about passive and active components at SMK Muhammadiyah 3 Weleri currently still uses a system like schools in general, namely the teacher conveys material in front of the class by means of a blackboard with chalk or markers to provide examples or illustrations to students. This is evident from the minimal percentage of the average value in basic electricity and electronics lessons about passive and active components decreasing due to many obstacles in their learning, students find it difficult to remember in lessons, in delivering information that has been used so far, problems have been found, namely by using a system that conventional in the delivery of material. Students are less interested and motivated to follow the teacher's explanation. By using a multimedia system is expected as a good solution to be able to resolve or overcome existing problems